PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI LIND’S ICE CREAM DAN RESTO PAPANDAYAN SEMARANG - Andri Yanusman Amazihono (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
This research was conducted at Lind's Ice Cream and Resto Papandayan Semarang which aims to analyze and explain the influence of location and service quality on guest satisfaction, as well as to determine which variables have the most dominant influence on guest satisfaction. The method used in this research is a survey with quantitative analysis,. The number of samples in this study were 86 respondents who visited Lind's Ice Cream and Resto Papandayan Semarang. Based on the results of SPSS calculations, the hypothesis at the tested level is significant and has a positive effect on the regression equation,And it is proven that the service quality variable has the most dominant effect on guest satisfaction with a regression coefficient of 0.794. The conclusion of this study is that The quality of service that has the most positive effect on guest satisfaction at Lind's Ice Cream and Resto Papandayan Semarang.